Movements and Behaviour of Target Fishes in the Marine Ranching Area Determined by Biotelemetry - Franco Meléndez, Milagros Teresa (2014)
Descargue el texto completo en el repositorio institucional de la Pukyong National University: https://repository.pknu.ac.kr:8443/handle/2021.oak/1395